Antiepileptic Effect and Safety Profile of Rapamycin in Pediatric Patients With Tuberous Sclerosis Complex - Sadowski, Krzysztof; Sijko, Kamil; Domańska-Pakieła, Dorota; Borkowska, Julita; Chmielewski, Dariusz; Ulatowska, Agata; Józwiak, Sergiusz; Kotulska, Katarzyna (Frontiers in Neurology, 2022)
Background Epilepsy develops in 70–90% of children with Tuberous Sclerosis Complex (TSC) and is often resistant to medication. Treatment with mTOR pathway inhibitors is an important therapeutic option in drug-resistant epilepsy associated with TSC. Our study evaluated the antiepileptic effect of rapamycin in the pediatric population of patients diagnosed with TSC. Methods This single center, open-label study evaluated safety and anti-epileptic efficacy of 12 months of rapamycin treatment in 32 patients aged from 11 months to 14 years with drug-resistant TSC- associated epilepsy. Results After the first 6 months of treatment, the improvement in seizure frequency, defined as at least a 50% reduction in the number of seizures per week compared to baseline, was seen in 18 individuals (56.25%). We observed no change in 12 individuals (37.5%) and worsening, defined as increase in the number of seizures—in 2 patients (6.25%). The overall improvement defined as at least a 50% reduction in seizure frequency was found in 65.6% of all patients after 12 months with 28% of patients obtaining complete remission. Another five patients experienced at least an 80% reduction in the frequency of seizures. Concomitant treatment with vigabatrin, and to a much lesser extent topiramate and levetiracetam, was an additional favorable prognostic factor for the success of the therapy. A linear relationship between the cumulative dose of rapamycin and its therapeutic effect was observed. The safety profile of the drug was satisfactory. In none of the observed cases did the adverse events reach the level that required withdrawal of the rapamycin treatment. The reason for dropouts was insufficient drug efficacy in 3 cases. Conclusions Long-term use of rapamycin, especially in combination with vigabatrin, might be a beneficial therapeutic option in the treatment of drug-resistant epilepsy in children with TSC.